The diagnostic role of diffusion weighted imaging in addition to dynamic contrast MR mammography in assessment of breast cancer patients after surgical treatment - Safaa Ibrahim Saif Elnasr; Maha Husein Helal; Rasha Wesam Abdelrahman; Soha Talaat Hamed (Cairo : Safaa Ibrahim Saif Elnasr, 2015)
Objective: To assess the additive role of Diffusion weighted imaging (DWI) in addition to dynamic contrast-enhanced magnetic resonance mammography (DCE-MRM) in evaluating breast cancer patients who underwent surgery (conservative or radical) and radiotherapy.Patients and methods: 60 female patients were included in this prospective study. This study was conducted at both Kasr El-Ainy hospital, radiology department (Women{u2019}s imaging unit) and National Cancer Institute (N.C.I) from March-2013 until March 2015. All cases underwent either breast conservative therapy (BCT) or radical mastectomy at least 6 months before doing their MRI. Recurrence or post-operative complications were suspected by clinical examination. Mammography and breast US were done followed by MRI examination. DCM was done with DWI with b values of (0, 50, and 850). Pathology was the gold standard. Results: out of the 60 patients, 27 were pathologically proven as malignant lesions compared to 33 patients with variable spectrum of post operative changes. In our study, DCE- MRI was superior to DWI in diagnosis of malignant lesions with 2 false positive cases and no false negative cases while DWI showed 3 false negative cases and 4 false positive cases. DCE-MRI sequence & DWI showed sensitivity (100% ,88.9%), specificity (93.9% , 87.9%), PPV (93.1% , 88.9%), NPP (100% , 90.6%) & accuracy (96.7% , 88.3%) respectively .Conclusion: Although DWI is considered a promising diagnostic tool in the diagnosis of breast cancer, its interpretation requires awareness of its possible pitfalls, weakness and strengths. Better results are obtained by combing DWI with dynamic sequences. DWI possibly can be an alternative to contrast injection at certain conditions as in patients with renal impairment
Thesis (Ph.D.) - Cairo University - Faculty of Medicine - Department of Radio-diagnosis
Issued also as CD
Keywords: Breast cancer; Diffusion Weighted Imaging; Surgical scarring